Tamamo the fox maiden and other Asian stories : a cautionary fables & fairytales book - Spike, 1978-; Ashwin, Kate; McDonald, Kel (Iron Circus Comics, 2018)
Presents a collection of graphic-novel adaptations of classic cautionary fables and fairy tales from Tibet, India, Indonesia, China, Japan, and Korea, full of flying ogres, vengeful spirits, trickster animals, and helpful household appliances like teapots.